Documentation of suicidality in connection with specialised healthcare for physical conditions: a retrospective review of somatic medical records prior to suicide in Sweden - Margda Waern; Åsa Westrin; Elin Fröding; Sara Lindström; Tabita Sellin; Erik Bergqvist; Nina Palmqvist Öberg; Anna Ehnvall (BMJ Open)
Objectives To evaluate whether suicidality was documented prior to suicide in patients in contact with specialised somatic healthcare providers for physical conditions and to identify factors related to such documentation.Design and settings Retrospective cohort study in which medical records from specialised somatic (non-psychiatric) healthcare services (internal medicine, infectious disease, surgery, urology, etc) in 20 of Sweden’s 21 regions were reviewed up to 2 years before suicide.Participants Those who died by suicide in Sweden 2015 and had received specialised somatic healthcare for a diagnosed physical condition were included, n=468 (331 men and 137 women).The outcome variable Documentation of suicidality (ie, death wishes, suicidal thoughts, plans, attempts and notations of known suicidality or elevated suicide risk). Potential associations of patients’ characteristics and clinical factors with the outcome were tested in logistic regression models.Results Of the 468 patients, 111 (24%) were positive for the outcome variable Documentation of suicidality, regardless of whether they were assessed as suicidal or not. Elevated suicide risk was noted in 27 patients (6% of the total cohort). Multivariate logistic regression analysis showed that experience of distress (OR: 4.81; 95% CI: 1.96 to 11.81), contact with psychiatric services (OR: 4.68; 95% CI: 2.60 to 8.43), psychiatric comorbidity (OR: 4.33; 95% CI: 2.41 to 7.76) and female sex (OR: 2.91; 95% CI: 1.68 to 5.06) were independently associated with documentation of suicidality. A third (36%) had a doctor consultation in specialised somatic healthcare during their last month of life. Of these, 17% were assessed for suicidality, and elevated suicide risk was noted in 7%.Conclusions Documentation of suicidality was observed in one quarter of patients who received specialised somatic healthcare for physical conditions and subsequently died by suicide. These results indicate a need to increase clinician awareness of suicidal issues and assessments and to integrate questions about mental health into specialised somatic practice.